Acute Respiratory Failure after Administration of Hydrogen Peroxide as an Emetic in a Cat - Leona Rauserova-Lexmaulova; Carlos Agudelo; Barbara Prokesova (Case Reports in Veterinary Medicine)
Objective and Case Summary. This case report describes a 5-year-old domestic short-haired cat that was orally administered with 4 mL of 3% hydrogen peroxide by the owner after suspecting ingestion of a foreign body by the cat. Shortly after the administration, the cat developed severe respiratory distress. Thoracic radiography showed an interstitial-to-alveolar pulmonary pattern, while echocardiography and heart injury markers ruled out a cardiac origin. Intensive management with oxygen, diuretics, bronchodilators, and sedation resulted in survival of the cat without further respiratory complications. New and Unique Information Provided. To the best of our knowledge, this is the first report of a lung injury and acute respiratory failure after administration of hydrogen peroxide in a cat with successful management.